2016
DOI: 10.1021/acs.analchem.6b00668
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Benzenediboronic-Acid-Induced Aggregation of Gold Nanoparticles: Application to Hydrogen Peroxide Detection and Biotin–Avidin-Mediated Immunoassay with Naked-Eye Detection

Abstract: Hydrogen-peroxide (H2O2)-induced growth of small-sized gold nanoparticles (AuNPs) is often implemented for H2O2 sensing and plasmonic immunoassay. In contrast, there is little-to-no information in the literature regarding the application of H2O2-inhibited aggregation of citrate-capped AuNPs. This study discloses that benzene-1,4-diboronic acid (BDBA) was effective in driving the aggregation of citrate-capped AuNPs through an interaction between α-hydroxycarboxylate of citrate and boronic acids of BDBA. The H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…The successful visual detection of urine glucose in original sample show its applicability for on-site identification of the healthy status of a diabetes patient. Finally, the GNRs-based method for sensitive detection of H 2 O 2 can be used for other H 2 O 2 -based sensing applications, (Chang and Ho, 2015;Liu et al, 2014;Wang et al, 2012;Yang and Tseng 2016) such as GOx-based immunoassay as shown in Scheme S1 (Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful visual detection of urine glucose in original sample show its applicability for on-site identification of the healthy status of a diabetes patient. Finally, the GNRs-based method for sensitive detection of H 2 O 2 can be used for other H 2 O 2 -based sensing applications, (Chang and Ho, 2015;Liu et al, 2014;Wang et al, 2012;Yang and Tseng 2016) such as GOx-based immunoassay as shown in Scheme S1 (Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…The detection limit was calculated to be 50 nM according to 3σ rule. The detection limit is much lower than other plasmonic methods (Liu et al, 2014;Yang and Tseng, 2016). The excellent sensitivity to H 2 O 2 will provide a good prerequisite for the ultrasensitive H 2 O 2 -mediated glucose detection.…”
Section: Z Zhang Et Almentioning
confidence: 87%
“…The red-shift band of the UV/vis spectra and the red-to-blue color change are characteristic of Au NP aggregation. The aggregation should contribute to the covalent interaction between boronate in BDBA and citrate on the surface of Au NPs (Figure 1B) [31,32,33,34]. However, the mixture of BDBA/H 2 O 2 did not cause significant changes in the color and absorption spectrum of Au NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The boronate group in a fluorescent probe is usually removed by H 2 O 2 to yield its corresponding phenol form, thus resulting in an increase/decrease of the fluorescence intensity or a shift of the fluorescence peak. More interestingly, we also noticed that boronic acid can react with citrate to form a boronic acid–citrate complex and the citrate-capped Au/Ag NPs could be simply prepared [31,32,33,34]. Inspired by these facts, herein we conceived a simple electrochemical strategy for the sensitive and selective detection of H 2 O 2 by converting a liquid-phase colorimetric assay into an electrochemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that 1.25 μmol dm -3 MPBA can induce the aggregation of 1 nmol dm -3 Au NPs efficiently. Tseng et al 35 reported the boronic acids of BDBA could react with the α-hydroxycarboxylate of citrate, triggering the aggregation of citrate-capped Au NPs. Based on the report, we speculated that the driving force for the MPBA-induced nanoparticle aggregation could arise from the binding of citrate to boronic acids of MPBA and formation of Au-S bond between Au surface and -SH group of MPBA.…”
Section: Aggregation Of Citrate-capped Au Nps Induced By Mpba and Bdbamentioning
confidence: 99%